Kualitas Embrio pada Sapi Simmental dan Limousin dengan Kadar Protein Pakan Berbeda - Hardiyanto, D.; Sumantri, C.; Zamanti, D. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
Enhancement beef population could be conducted using the MOET (multiple ovulation, the embryo transfer). This method is done to ensure the quality of embryos have high production. Determination of embryo quality on this method gave fed with 15%-20% protein levels. This research was aim to evaluate influenced of different gave fed againt different breed. The evaluation was done by observing at the influence of the environment against the production of embryos. The assessment was conducted using factorial design experiment. The evaluation results showed average production of embryos in different breeds was not significant (P>0.05) influence to embryo quality quality. An important factor for obtaining the production of viable embryo transfer were not linked to individual breeds